Ordinary Oralities Everyday Voices in History - Hoegaerts, Josephine; Schroeder, Janice (De Gruyter, 2023)
Histories of voice are often written as accounts of greatness: great statesmen, grands discours, famous singers. But for most, life consists of private conversations, intimate whispers, hot gossip or ceaseless quarrels. The volume suggests an extended practice of eavesdropping: it listens in on more mundane aspects of vocality - who speaks, whose voices resound in history - while questioning the modern equation between speech and representation.